Safeguarding literary and intellectual property in the age of artificial intelligence: Legal frameworks, opportunities, and challenges - Larbi, Aziz; Nateche, Khelifa (The International tax journal, 2025)
The right to privacy, a fundamental principle in global legal systems, is increasingly scrutinized amid rapid digital transformation. Enshrined in international and domestic legislation, it seeks to protect personal data from escalating cyber threats. This paper traces the evolution of privacy rights from traditional domains to digital platforms, highlighting adaptive legal and institutional responses. It calls for an integrated legal framework that combines strong safeguards, institutional accountability, and public awareness to address emerging challenges. Ultimately, the study offers strategic recommendations to align technological innovation with the protection of individual rights in the digital era.